2005
DOI: 10.1089/vbz.2005.5.20
|View full text |Cite
|
Sign up to set email alerts
|

Arbovirus Circulation, Temporal Distribution, and Abundance of Mosquito Species in Two Carolina Bay Habitats

Abstract: Carolina bays, a type of geomorphic feature, may be important in the ecology of mosquito vectors in South Carolina. Their hydrology varies from wetland habitats with marked flooding/drying regimes to permanently flooded spring-fed lakes. Moreover, they possess characteristics that contribute to the support of a particularly abundant and diverse invertebrate fauna. Although it has been estimated that 2,700+ bays exist in South Carolina, approximately 97% have been altered; < or = 200 bays remain intact, and onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…16,17,42 † Relative number of EEEV-positive pools detected: 0, never isolated; 1, rarely isolated; 2, occasionally isolated; 3, commonly isolated. 6,9,11,18,19,[43][44][45][46] ‡ Distance from forest margin when host seeking: 0, < 1 km; 1, 1-3 km; 2, 3-8 km; 3, > 8 km. 45,[47][48][49][50][51] § Population abundance in CDC light traps at epizootic site during summer of 2006: 0, < 1% of total; 1, 1-10%; 2, 10-20%; 3, > 20% (Mukherjee and others, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17,42 † Relative number of EEEV-positive pools detected: 0, never isolated; 1, rarely isolated; 2, occasionally isolated; 3, commonly isolated. 6,9,11,18,19,[43][44][45][46] ‡ Distance from forest margin when host seeking: 0, < 1 km; 1, 1-3 km; 2, 3-8 km; 3, > 8 km. 45,[47][48][49][50][51] § Population abundance in CDC light traps at epizootic site during summer of 2006: 0, < 1% of total; 1, 1-10%; 2, 10-20%; 3, > 20% (Mukherjee and others, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…6,9,11,18,19,[43][44][45][46] ‡ Distance from forest margin when host seeking: 0, < 1 km; 1, 1-3 km; 2, 3-8 km; 3, > 8 km. 45,[47][48][49][50][51] § Population abundance in CDC light traps at epizootic site during summer of 2006: 0, < 1% of total; 1, 1-10%; 2, 10-20%; 3, > 20% (Mukherjee and others, unpublished data). ¶ Potential for species to be enzootic or maintenance vector: 0, no potential; 1, minor potential; 2, moderate potential; 3, major potential.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, TSV was originally isolated in 1960 from Anopheles crucians mosquitoes in southern Alabama [6]. Surveillance studies have shown that TSV can be found from North Carolina and Texas to Florida [7][8][9]. Although TSV has been most frequently isolated from Anopheles crucians, it has also been found in Anopheles quadrimaculatus, Psorophora confinnis, Aedes atlanticus, Aedes mitchellae, Culex nigripalpus, and Mansonia peturbans [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Surveillance studies have shown that TSV can be found from North Carolina and Texas to Florida [7][8][9]. Although TSV has been most frequently isolated from Anopheles crucians, it has also been found in Anopheles quadrimaculatus, Psorophora confinnis, Aedes atlanticus, Aedes mitchellae, Culex nigripalpus, and Mansonia peturbans [7,9]. Serological studies have shown that TSV infects a variety of wild and domestic vertebrates [7][8][9], as well as humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation